Reproductive resilience: putting pollen grains in two baskets. (March 2022) - Rutley, Nicholas; Harper, Jeffery F.; Miller, Gad
Abstract : To ensure reproductive success, flowering plants produce an excess of pollen to fertilize a limited number of ovules. Pollen grains mature into two distinct subpopulations – those that display high metabolic activity and elevated reactive oxygen species (ROS) levels immediately after hydration (high-ROS/active), and those that maintain an extended period of dormancy with low metabolic activity (low-ROS/inactive/arrested/dormant). We propose that the dormant pollen serves as a backup to provide a second chance for successful fertilization when the 'first wave' of pollen encounters an unpredictable growth condition such as heat stress. This model provides a framework for considering the role of dormancy in reproductive stress tolerance as well as strategies for mitigating pollen thermovulnerability to daytime and night-time warming that is associated with global climate change. Highlights: The thermovulnerability of pollen in flowering plants poses a serious threat to food security as the average day- and night-time temperatures rise due to global warming. Flowering plants have evolved 'a pollen in two baskets' strategy for increasing the chances of successful fertilization by producing pollen that is immediately active and ready to germinate after hydration, and a separate subpopulation of backup pollen that remains in an extended low-activity state of dormancy. Night-time warming episodes might directly impact on reproductive success by disrupting the opportunity for backup pollen to utilize the relatively cool nights to engage in a second attempt to fertilize ovules. FACS provides an experimental strategy to separate and study subpopulations of active and backup pollen.